2016
DOI: 10.1126/science.aad2087
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for leucine sensing by the Sestrin2-mTORC1 pathway

Abstract: Eukaryotic cells coordinate growth with the availability of nutrients through mTOR complex 1 (mTORC1), a master growth regulator. Leucine is of particular importance and activates mTORC1 via the Rag GTPases and their regulators GATOR1 and GATOR2. Sestrin2 interacts with GATOR2 and is a leucine sensor. We present the 2.7-Å crystal structure of Sestrin2 in complex with leucine. Leucine binds through a single pocket that coordinates its charged functional groups and confers specificity for the hydrophobic side ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
353
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 373 publications
(358 citation statements)
references
References 46 publications
5
353
0
Order By: Relevance
“…Subsequent biochemical and structural analyses established that Sestrin2 is a direct leucine sensor upstream of mTORC1 that binds and inhibits GATOR2 function in the absence of leucine, and dissociates from it upon leucine binding (Saxton et al, 2016a;Wolfson et al, 2016). Furthermore, the affinity of Sestrin2 for leucine determines the sensitivity of mTORC1 signaling to leucine in cultured cells, demonstrating that Sestrin2 is the primary leucine sensor for mTORC1 in this context.…”
Section: Upstream Of Mtorc1mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent biochemical and structural analyses established that Sestrin2 is a direct leucine sensor upstream of mTORC1 that binds and inhibits GATOR2 function in the absence of leucine, and dissociates from it upon leucine binding (Saxton et al, 2016a;Wolfson et al, 2016). Furthermore, the affinity of Sestrin2 for leucine determines the sensitivity of mTORC1 signaling to leucine in cultured cells, demonstrating that Sestrin2 is the primary leucine sensor for mTORC1 in this context.…”
Section: Upstream Of Mtorc1mentioning
confidence: 99%
“…Both D. melanogaster and C. elegans do have a Sestrin homolog however, and dmSestrin also binds leucine . Interestingly, both ceSestrin and dmSestrin contain subtle differences in their leucine binding pockets predicted to reduce their affinity for leucine relative to human Sestrin2, likely enabling the sensing of physiologically relevant leucine levels in these organisms (Saxton et al, 2016a).…”
Section: Evolutionary Conservation Of the Tor Pathwaymentioning
confidence: 99%
“…Binding to Raptor requires RagA/B to be GTP loaded, while RagC/D must be GDP loaded. Nutrients are thought to induce the RagA/B GTP -RagC/D GDP active state via a series of dedicated sensors that, in turn, control GTPase Activating Proteins (GAPs) and guanine nucleotide exchange factors (GEFs) specific for either Rag component (Bar-Peled et al, 2012;Barad et al, 2015;Chantranupong et al, 2016;Saxton et al, 2016;Wolfson et al, 2016;Zoncu et al, 2011). For example, the Gator1 complex has been shown to function as a GAP that promotes GTP hydrolysis by RagA/B, thus causing mTORC1 detachment from the lysosome when nutrient levels are low Panchaud et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This research group also identified the cytosolic protein SESTRIN2 as a leucine sensor involved in mTORC1 regulation. Like CASTOR1, SESTRIN2 interacts with GATOR2 in the absence of its amino acid ligand to inhibit mTORC1 (25,26), suggesting that the GATOR2 complex represents a key hub in mTORC1 regulation by amino acids.…”
Section: Liquid Phase Separationmentioning
confidence: 99%